Stability of Gøsta Esping-Andersen's "The three worlds of welfare capitalism" - Andreas Tiemann (Luxembourg Income Study (LIS), 2006)
Since its first publication in 1990, Esping-Andersen's typology of 'The Three Worlds of Welfare Capitalism' has loomed incomparably large over the area of comparative social politics. This paper uses the concept of stability, researching comprehensively whether the construct 'Three Worlds of Welfare Capitalism' has been valid for over 20 years despite the varying outcomes of the 18 countries' social policy. By using recent data, a nearly complete replication of Esping-Andersen's original indices was accomplished. The results of the research at hand explicitly reveal that Esping-Andersen's fundamental logic now shows stark discrepancies. Subsequently, in order to search for an appropriate typology to subsume various kinds of social policy, turning away from the alleged 'Three Worlds of Welfare Capitalism' seems indispensable.
Keywords: 330; Sozialstaat; Klassifikation; Theorie; Schätzung; Welt